Effectiveness of Licensing Services Through the Sicantik Cloud Application in the Department of Capital Investment and One-Door Integrated Services in Batu Bara District - Ahmad Bukhari; Humaizi; Nurman Achmad (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine The Effectiveness of Licensing Services via the SiCANTIK Cloud Application at the Batu Bara Regency Investment and One-Stop Integrated Services Service. This type of te research is descriptive with a qualitative approach. The research location is at the Batu Bara Regency Investment and One-Stop Integrated Services. informant selection techniques purposive sampling. This research uses data collection techniques: observation, interviews and documentation. The results of this research are that Licensing Services via the SiCANTIK Cloud Application at the Batu Bara Regency Investment and One-Stop Integrated Services Service are still not effective when viewed based on several indicators in the theory of effectiveness according to Duncan in steers, including (1) goal achievement; (2) integration; and (3) Adaptation of the SiCANTIK Cloud Application in providing licensing services in Batu Bara Regency